Analisisis Kinerja Sprinkler Mini Meganet 24 D Netafim Terhadap Variasi Debit dan Jarak Penempatan Sprinkler - I Dewa Gede Jaya Negara; Ida Bagus Giri Putra; Anid Supriadi; Made Anggitha Dewi (LPPM Universitas Mataram, 2021)
Currently, there are many efficient and effective sprinkler irrigation tools on the market, so it is necessary to be careful in choosing for irrigation. Among them, the Meganet 24D Netafim, including the type of irrigation tool, which still needs testing to know its performance. This study aims to examine the sprinkler irrigation performance of Meganet 24D Netafim, on variations in flow rate and distance between sprinklers, related to irrigation uniformity (CU) and irrigation radius (Rn). This test was carried out on an area of about 1 acre, at a flow rate of Q1=0.42/sec, Q2=0.51 l/sec, Q3=0.52/sec, Q4=0.56 and the test sprinkler distance, r1=2 ,5m, r2=3m,r3 = 3.5m and r4 = 4m. The results of data analysis are presented in the form of tables and graphs and concluded descriptively. The results showed that, in all variations of Q and sprinkler spacing r1, r2, r3 obtained irrigation uniformity (CU) above 85% which was classified as high, while in the r4, Q1 and Q2 tests, CU was obtained below 85% which was considered low. All discharge variations, showing irrigation radius (R) about 5 m. So at r4 sprinkler spacing, it is not recommended in irrigation applications.